Humanitarian OpenStreetMap Team Role Towards Mapping in Indonesia - Putra, Muhammad Agiet; Whardana, Adithya Kusuma (LPPM of STIMIK ESQ, 2017)
This research aimed to describe the shape or the role of the Humanitarian OpenStreetMap Team in Indonesia. The main role of the Humanitarian OpenStreetMap Team is helping government agencies such as the BNPB, BPBDs, and others to be able to do digital mapping and able to make contingency planning as a scenario to cope with natural disasters. Then also to students with the aim of expanding the mapper community members who can help BPBDs in the vicinity. Noted there are 116 training ever conducted, with 2,777 participants involved, spread across 16 provinces in Indonesia. The method used is descriptive method, based on the literature that comes from the journal related to GIS and OSM, internal reports HOT, HOT and then also through the website. From this research, it was found that the areas that have been getting training from the HOT has successfully implemented the concept of digital mapping and manufacture of contingency planning, as well as more systematic in the handling of natural disasters